A comparison of physical activity, muscle strength, and sleep between people with type 2 diabetes in Kuwait and the UK: A cross-sectional study - Al Ozairi, Ebaa; Alsaeed, Dalal; Al Roudhan, Dherar; Voase, Nia; Pell, Jill P.; Ho, Frederick K.; Abdulla, Mohammed; Gray, Stuart R. (Frontiers in Endocrinology, 2022)
Background The aim of the current study was to determine the prevalence of low muscle strength and to evaluate physical activity and sleep characteristics in people with type 2 diabetes in Kuwait. Additionally, equivalent data from the UK Biobank cohort was compared. Methods People with type 2 diabetes from the UK Biobank (n=23,570) and Kuwaiti cohort (n=3,135) were included in the cross-sectional study. Self-reported sleep, physical activity and muscle strength were compared between the cohorts, using linear and logistic regression, with adjustment for age, sex and duration of diabetes. Results Physical activity levels (-937 (-1097,-851) Met-min/week: standardized B-coefficient -0.42 (-0.47, -0.37)) and grip strength (3.2 (-3.58,-2.82) kg: standardized B-coefficient (-0.29 (-0.32, -0.26)) were lower in the Kuwaiti cohort and the odds of having short sleep (OR 1.32 (1.19,1.46), being classed as inactive (OR 8.70 (7.59, 9.98) and having muscle weakness were higher (OR 1.88 (1.69, 2.09). These analyses were adjusted for age, sex and duration of diabetes. Conclusions The aim of the current study was to determine the prevalence of low muscle strength and to evaluate physical activity and sleep characteristics in people with type 2 diabetes in Kuwait. Additionally, equivalent data from the UK Biobank cohort was compared.